2003
DOI: 10.1271/bbb.67.139
|View full text |Cite
|
Sign up to set email alerts
|

Mepanipyrim, a Novel Inhibitor of Pharmacologically Induced Golgi Dispersion

Abstract: Mepanipyrim inhibited retrograde Golgi-to-ER trafficking induced by brefeldin A (BFA), nordihydroguaiaretic acid, clofibrate, and arachidonyltrifluoromethyl ketone in NRK and other types of cells, but did not inhibit anterograde trafficking of Golgi-resident proteins translocated to ER by BFA and newly synthesized VSV-G. However, mepanipyrim did not block the TGN38 dispersion induced by any of these compounds. Mepanipyrim acted on the Golgi, and swollen vesicular Golgi structures were formed and similar struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Sonogashira cross-coupling of 205 with propyne furnishes the alkynyl derivative 206 in 97 % yield. Finally, amination of 206 with aniline under Buchwald-Hartwig amination conditions [170][171][172][173] produces the fungicide mepanipyrim 207 [174,175] in 81 % yield (Scheme 38). [169] The metalation of the uracil scaffold can be achieved by selective deprotonation of 2,4-dimethoxypyrimidine.…”
Section: Tmpmgcl·licl and Related Magnesium Basesmentioning
confidence: 99%
“…Sonogashira cross-coupling of 205 with propyne furnishes the alkynyl derivative 206 in 97 % yield. Finally, amination of 206 with aniline under Buchwald-Hartwig amination conditions [170][171][172][173] produces the fungicide mepanipyrim 207 [174,175] in 81 % yield (Scheme 38). [169] The metalation of the uracil scaffold can be achieved by selective deprotonation of 2,4-dimethoxypyrimidine.…”
Section: Tmpmgcl·licl and Related Magnesium Basesmentioning
confidence: 99%
“…The Golgi complex is fragmented by monensin, but remains localized in the perinuclear region (26). in BFa-treated cells, Golgi components are redistributed to the endoplasmic reticulum or intermediate compartments (21). Golgi staining in nonactin-treated cells was similar to that in control cells, indicating that cytoplasmically dispersed punctate immunofluorescence stains in nonactin-treated cells are caused by fragmentation of the Golgi apparatus.…”
Section: Effects Of Nonactin On Intracellular Glycosylation Inhibitionmentioning
confidence: 66%
“…Significant efforts have been made to determine the mechanism(s) underlying glycosylation trafficking in cells, particularly with the aid of inhibitors of trafficking, which are powerful tools in these studies (21). However, limited compounds that affect intracellular trafficking processes have been identified to date.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether Golgi disassembly and Golgi-ER fusion are required for SREBP2 activation, we treated monocytic myeloid cells with mepanipyrim. Mepanipyrim has been reported to inhibit Golgi disassembly and BFA-induced retrograde Golgi-to-ER trafficking through a mechanism that is not fully understood (Nakamura et al, 2003). We found that mepanipyrim prevented hypoxiainduced Golgi disassembly ( To further support our hypothesis that hypoxia-induced SREBP2 translocation occurs due to Golgi-ER fusion and consequent Golgito-ER retrograde transport, we treated monocytic myeloid cells with nocodazole and Brefeldin A (BFA), which are two commonly used chemicals to induce Golgi disassembly through different mechanisms (Debose-Boyd et al, 1999).…”
Section: Hypoxia-induced Golgi Disassembly Activates Srebp2 For Chole...mentioning
confidence: 99%